2020
DOI: 10.3390/su12051785
|View full text |Cite
|
Sign up to set email alerts
|

Children’s and Mothers’ Achievement Goal Orientations and Self-Efficacy: Dyadic Contributions to Students’ Well-Being

Abstract: Starting from the basic idea that identifying predictive family factors for children's well-being is among the levels of the psychology of sustainable human development, our study aimed to investigate the impact of mothers' achievement goal orientations and parental self-efficacy on their children's academic well-being, considering children's own achievement goals as a mediator variable. The entire sample comprised 350 participants: 175 children (42.86% boys) and their respective mothers. Children were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 115 publications
(213 reference statements)
0
8
0
Order By: Relevance
“…In the study conducted by Sevigny and Loutzenhiser (2010), a relationship was found between mothers' general self-efficacy and relational functionality levels and their children's psychosocial adjustment. In another research, it was recorded that parental self-efficacy is determinant on children's goal orientation and well-being (Curelaru et al, 2020). Bojczyk et al (2018) found that high self-efficacy in mothers created a more effective home learning experience for the child, and emphasized the link between the home learning experience and theirs vocabulary skills.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study conducted by Sevigny and Loutzenhiser (2010), a relationship was found between mothers' general self-efficacy and relational functionality levels and their children's psychosocial adjustment. In another research, it was recorded that parental self-efficacy is determinant on children's goal orientation and well-being (Curelaru et al, 2020). Bojczyk et al (2018) found that high self-efficacy in mothers created a more effective home learning experience for the child, and emphasized the link between the home learning experience and theirs vocabulary skills.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…In addition, in-depth studies investigating the effects of different variables on children's psychiatric symptom severity levels can be planned. In the study conducted by Curelaru et al (2020); it was found that mothers' high self-efficacy caused children to have high learning self-efficacy, and high learning self-efficacy caused lower depressive symptoms. In the study conducted by Teti and Gelfand (1991), it was emphasized that parenting behavior can play a substantial role in determining the psychosocial risk of the baby.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…The importance of this concept has been analyzed in various contexts. For example, in dyadic relationships (mother-child or teacher-student) the perceived self-efficacy of one partner (e.g., mother or teacher) has been shown to be a significant predictor of the self-efficacy of the other partner (e.g., child or student) (Corkett et al, 2011;Curelaru et al 2020). When this concept is applied to investigate teaching self-efficacy, teachers' role requests a contextualization of selfefficacy in the area of designing and managing education.…”
Section: Problem Statementmentioning
confidence: 99%
“…A reasonable ground for this isolation is that many recent studies have been published investigating the relationships between the construct of goal orientation and self-efficacy (Curelaru, 2020); goal orientation and emotional intelligence and burnout (Supervía et al, 2020a); goal orientation and engagement and self-concept (Supervía et al, 2020b); goal orientation and emotional intelligence and burnout (Supervía and Bordás, 2020); goal orientation and positive coping strategy and motivational beliefs (Subaşı, 2020); goal orientation and academic achievement (Giota and Bergh, 2020;Moghimi, 2020); goal orientation and individual characteristics (Lamm et. al., 2020); and goal orientation and motivation (Hidajat et al, 2020).…”
Section: The Importance Of Academic Goal Orientationmentioning
confidence: 99%